Occurrence and seasonal variation of equine estrogens, equilin and equilenin, in the river water of Japan: Implication with endocrine-disrupting potentials to Japanese medaka (Oryzias latipes). (August 2018) - Ishibashi, Hiroshi; Uchida, Masaya; Yoshimoto, Keisuke; Imamura, Yuta; Yamamoto, Ryoko; Ikenaka, Yoshinori; Kawai, Masahito; Ichikawa, Nobuhiro; Takao, Yuji; Tominaga, Nobuaki; Ishibashi, Yasuhiro; Arizono, Koji
Abstract: In this study, we determined the concentration of equine estrogens, such as equilin (Eq) and equilenin (Eqn), in the river water collected from nine research stations in Hokkaido, Japan. The LC–MS/MS analysis revealed that Eq concentrations were 2.7 ± 6.7, 0.22 ± 0.12, and 1.2 ± 0.64 ng/L in Sep 2015, Feb 2016, and Jul 2016, respectively. Eqn had concentration levels similar to those of Eq. Comparison of the concentrations at nine research stations showed that seasonal variation was observed in the detected Eq and Eqn concentration levels. This study was the first to show the occurrences and seasonal variation of Eq and Eqn in the river water of Japan. We further investigated the reproductive and transgenerational effects of Eq in Japanese medaka ( Oryzias latipes ) exposed to 10, 100, and 1000 ng/L for 21 days and assessed the transcriptional profiles of the estrogen-responsive genes in the livers of both sexes. The reproduction assay demonstrated that 1000 ng/L of Eq adversely affected the reproduction (i.e. fecundity) in the F0 generation and that the hatching of F1 generation fertilized eggs was reduced in the 100 and 1000 ng/L treatment groups. Our qRT-PCR assay revealed that the mRNA expression levels of hepatic vitellogenin 1 and 2, choriogenin L and H, and estrogen receptor α were significantly up-regulated in males exposed to 100 and/or 1000 ng/L of Eq. In contrast, the transcriptional levels of several genes, such as pregnane X receptor and cytochrome P450 3A, were down-regulated in the livers of males after the 21-d exposure. These results suggest that Eq has endocrine-disrupting potential such as reproductive and transgenerational effects by the modulation of hepatic estrogen-responsive genes expression on medaka. Graphical abstract: Image 1 Highlights: The occurrences of equilin and equilenin in the river of Japan were verified. Equilin affected the reproduction (i.e. fecundity) in the F0 adult medaka. Equilin affected the hatching of fertilized eggs in the F1 medaka. Equilin has endocrine-disrupting potentials on medaka. Abstract : Occurrence, seasonal variation and endocrine-disrupting potentials of equine estrogens.